Cracking the code: uncovering the factors that drive COVID‑19 standard operating procedures compliance among school management in Malaysia - Karuppiah, Karmegam; Ali, Nina Fatma; Praveena, Sarva Mangala; Ahmad, Noor Sakinah; Ramdas, Murugadas; Mohammad Yusof, Nur Athirah Diyana (Nature Publishing Group, 2024)
Malaysia’s government’s decision to reopen schools during the COVID-19 outbreak, especially for students taking important exams, has alarmed the public. However, the Ministry of Education has implemented a COVID-19 Standard Operating Procedure (SOP) for educational institutions. The school management’s ability to protect children from COVID-19 rests on their understanding, attitudes, and practices regarding COVID-19 SOP compliance. This study investigated Selangor, Kuala Lumpur, and Putrajaya school management’s COVID-19 SOP compliance determinants. Multistage sampling was used to sample 740 school management from Kuala Lumpur, Putrajaya, and Selangor. A selfadministered questionnaire collected sociodemographic, occupational, and lifestyle data, knowledge, attitude, and practice of COVID-19 SOP compliance. The school management had good knowledge, attitude, and practice toward COVID-19 SOP. Monthly income, school location, smoking status, and physical activity differed significantly from KAP (p < 0.05). The correlation between KAP showed a significant relationship with the values (r = 0.348, p < 0.001) and (r = 0.358, p = 0.003). Nine independent variables strongly predicted SOPs compliance practice in multiple linear regression: knowledge, attitude, age, source of knowledge; Ministry of Health, physical activities, type of infectious disease exposed; Tuberculosis and Measles (p < 0.05). The data indicate that school management exhibits good knowledge, attitude, and compliance with SOPs during the pandemic. School management oversees SOPs, and to keep schools safe, management must analyse hazards and take action. Therefore, knowledge and attitude are expected to determine factors of practice toward COVID-19 SOP compliance.